Structure and performance in the Portuguese banking industry in the nineties - Mendes, Victor (2018)
In this paper we study the structure-performance relationship in the Portuguese banking industry during the nineties. The hypothesis of pure collusion, efficient structure, modified efficient structure and hybrid collusion/efficiency are tested using a direct measure of efficiency. Our results endorse the hybrid collusion/efficiency hypothesis in the first half of the nineties. However, after 1994 results lend some support to the modified efficient structure hypothesis. Competition at the local level remains important throughout the decade, suggesting that banks in less competitive local markets exert some level of market power and exhibit superior performances.